Analysis of Zakat Collection Based on Sharia Compliance Principles Before and After the Pandemic - Singgih Mahardhika (Jurnal Ilmiah Ekonomi Islam, 2023)
In this research, the authors analyzed sharia compliance and its application in the field of collecting BAZNAS Berau Regency before and during the pandemic. The research aimed to determine whether BAZNAS Berau Regency has carried out the fundraising management function following the provisions set by BAZNAS RI contained in IKSOPZ. This research used a quantitative method with a case study approach, Index of Sharia Compliance in Zakat Management Organization (IKSOPZ) analysis, and Analytical Hierarchy Process (AHP) to analyze the improvement strategy of sharia performance at BAZNAS Berau Regency. The results showed that BAZNAS Berau Regency has not fully complied with sharia, especially in managing escrow of zakat, infaq, and alms funds. The result of AHP analysis on improvement initiatives of the sharia performance at BAZNAS Berau Regency showed that it has to do a book-transfer mechanism from a conventional bank account to a sharia bank account. The research is expected to obtain results from the implementation of sharia compliance in BAZNAS Berau Regency that can be used as a benchmark for zakat regulators to improve zakat management rules following sharia principles.